The development of digital collection platform under responsible innovation framework: A study on China's non-fungible token (NFT) industry - Dandan He; Zheng Liu; Qingqing Yang; Lei Ma (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The combination of non-fungible token (NFT) with paintings, music, games, videos and other forms of creative content is an innovation to protect the copyright of authors. It digitizes physical works with unique labels. At present, the NFT industry is blooming in the area of digital collections in China, attracting increasingly more artists, art collectors and platform enterprises to interact. However, the NFT digital collection platform is facing challenges and growth limitations. This study adopts the theory framework of responsible innovation. Through semi-structured interview and secondary document review, it analyzes the positive and negative effects of China's NFT digital collections alongside technological, economical, ethical and social dimensions. The paper proposes four development paths to achieve responsible innovation of this emerging new business. Further discussion links NFT with open innovation dynamics, alongside areas for future research.
Keywords: 650; digital collection platform; non-fungible token (NFT); platform innovation; responsible innovation